(untitled) (American Journal of Technology and Applied Sciences, 2023)
This article discusses the issue of liability for cyberattacks in online dispute resolution (ODR). As ODR grows in popularity as a means of effective and affordable dispute resolution, questions arise regarding liability when the ODR platform itself is at risk from a cyberattack. Based on an analysis of relevant case law and legislation, the paper argues that the current legal framework is inadequate to address this issue of problem. A review of technological solutions points to blockchain as a promising tool for improving security and ensuring a better distribution of responsibility after an attack. However, technology alone is not enough. The document proposes legislative and policy changes to clearly delineate the responsibilities of ODR platform providers and users to prevent attacks. and a compensation fund model to support reparations in the event of attacks. By clarifying liability and providing compensation, these measures can contribute to the sustainable development of ODR as a fair and reliable means of dispute resolution.